Suppression of colonic oxidative stress caused by chronic ethanol administration and attenuation of ethanol-induced colitis and gut leakiness by oral administration of sesaminol in mice. Issue 18 (15th August 2022) - Ohira, Hideo; Oikawa, Daiki; Kurokawa, Yoichi; Aoki, Yuichi; Omura, Ayano; Kiyomoto, Kunio; Nakagawa, Wao; Mamoto, Rie; Fujioka, Yoshio; Nakayama, Toru
Abstract : Sesaminol may lower the risk of ethanol-related colorectal cancer by suppressing ethanol-induced oxidative stress in the colon as well as gut leakiness. Abstract : Chronic consumption of excess ethanol is one of the major risk factors for colorectal cancer (CRC), and the pathogenesis of ethanol-related CRC (ER-CRC) involves ethanol-induced oxidative-stress and inflammation in the colon and rectum, as well as gut leakiness. In this study, we hypothesised that oral administration of sesaminol, a sesame lignan, lowers the risk of ER-CRC because we found that it is a strong antioxidant with very low prooxidant activity. This hypothesis was examined using a mouse model, in which 2.0% v/v ethanol was administered ad libitum for 2 weeks with or without oral gavage with sesaminol (2.5 mg per day). Oral sesaminol administration suppressed the ethanol-induced colonic lesions and the ethanol-induced elevation of the colonic levels of oxidative stress markers (8-hydroxy-2′-deoxyguanosine, malondialdehyde, and 4-hydroxyalkenals). It consistently suppressed the chronic ethanol-induced expressions of cytochrome P450-2E1 and inducible nitric oxide synthase and upregulated heme oxygenase-1 expression, probably via the nuclear factor erythroid-derived 2-like 2 pathway in the mouse colon. Oral sesaminol administration also suppressed the chronic ethanol-induced elevation of colonic inflammation marker levels, such as those of tumour necrosis factor-α, interleukin-6, and monocyte chemoattractant protein-1, probably via the nuclear factor-kappa B pathway. Moreover, it prevented the chronic ethanol-induced gut leakiness by restoring tight junction proteins, giving rise to lower plasma endotoxin levels compared with those of ethanol-administered mice. All of these results suggest that dietary supplementation of sesaminol may lower the risk of ER-CRC by suppressing each of the above-mentioned steps in ER-CRC pathogenesis.